Controlling amphiphilic copolymer self-assembly morphologies based on macrocycle/anion recognition and nucleotide-induced payload release. Issue 9 (8th June 2016) - Ji, Xiaofan; Wang, Hu; Li, Yang; Xia, Danyu; Li, Hao; Tang, Guping; Sessler, Jonathan L.; Huang, Feihe
Abstract : We create polymeric self-assembly morphologies by exploiting the anion binding features of the so-called 'Texas-sized' molecular box. Abstract : We report here a new approach for creating diversiform copolymer-derived self-assembly morphologies that relies on macrocycle/anion recognition in aqueous media. This approach exploits the anion binding features of a water-soluble form of the so-called 'Texas-sized' molecular box. When this tetracationic receptor is added to an aqueous solution of an amphiphilic copolymer bearing tethered carboxylate anion substituents, binding occurs to form a macrocycle/polymer complex. As the concentration of the box-like receptor increases, the relative hydrophilic fraction of the copolymer complex likewise increases. This leads to changes in the overall morphology of the self-assembled ensemble. The net result is an environmentally controllable system that mimics on a proof-of-concept level the structural evolution of organelles seen in living cells. The macrocycle/anion interactions respond in differing degrees to three key biological species, namely ATP, ADP, and AMP, which may be used as "inputs" to induce disassembly of these vehicles. As a result of this triggering and the nature of the morphological changes induced, the present copolymer system is capable of capturing and releasing in a controlled manner various test payloads, including hydrophobic and hydrophilic fluorophores. The copolymer displays a low inherent cytotoxicity as inferred from cell proliferation assays involving the HUVEC and HepG2 cell lines.